Penetuan dosis pupuk nitrogen, fosfor, dan kalium optimum untuk padi sawah varietas bioemas agritan - Yati Astuti; Iskandar Lubis; Ahmad Junaedi (Jurnal AGRO, 2023)
Fertilizer requirements for each rice variety are different from other varieties. Research on the optimum dosage of fertilization on new superior varieties is needed to obtain optimum growth and yield. This study aims to determine the optimum dosage of N, P, and K fertilizer for the growth and productivity of lowland rice of the Bioemas Agritan variety. The research was conducted at Banten Assessment Institute for Agricultural Technology, from February 2022 to June 2022 on soils with very low C-organic and total N conditions. The study consisted of three parallel experiments, namely the N, and P, K fertilization experiment using a single factor randomized  complete block design which was repeated three times. Fertilizer dosages consist of five levels, namely 0, 50, 100, 150, and 200% of the reference dosage. Determination of the optimum dosage based on the maximum value of the relative yield quadratic equation. The optimum fertilizer dosage for the lowland rice variety Bioemas Agritan is 140,93% of the reference dosage or equivalent to 422,79 kg ha-1 urea, while the optimum dosage of P2O5 and K2O fertilizer cannot be determined.ABSTRAK Kebutuhan pupuk setiap varietas padi berbeda antara varietas satu dengan varietas lainnya. Penelitian dosis optimum pemupukan pada varietas unggul baru diperlukan untuk mendapatkan pertumbuhan dan hasil yang optimum. Penelitian ini bertujuan untuk menentukan dosis optimum pupuk N, P, K untuk pertumbuhan dan produktivitas padi sawah varietas Bioemas Agritan. Penelitian dilaksanakan di BPTP Banten, pada bulan Februari 2022 sampai dengan Juni 2022 pada tanah dengan kondisi C-organik dan N total sangat rendah. Penelitian terdiri atas tiga percobaan paralel yaitu percobaan pemupukan N, P, K menggunakan rancangan kelompok lengkap teracak faktor tunggal yang diulang sebanyak tiga kali. Dosis pupuk terdiri atas lima taraf yaitu 0, 50, 100, 150, dan 200 % dari dosis acuan. Penentuan dosis optimum berdasarkan nilai maksimum dari persamaan kuadratik hasil relatif. Dosis pupuk optimum untuk padi sawah varietas Bioemas Agritan adalah 140,93% dari dosis acuan atau setara dengan 422,79 kg ha-1 urea, sedangkan dosis optimum pupuk P2O5 dan K2Otidak dapat ditentukan.